Polarized Muslim audiences in Malaysia - Rozita Abdullah,; Rosidayu Sabran,; Mohd Faizal Kasmani,; Mohd Yahya Mohd Ariffin,; Kamaluddin Nurdin Marjuni,; Noor Adzrah Ramle, (Penerbit Universiti Kebangsaan Malaysia, 2019)
There have been a significant rise of local programs in TV stations in Malaysia. One form of the program that have been gaining interest is known as Islamic televangelism. Online focus groups discussion were conducted to understand audiences’ perception on Islamic televangelism programs. The interaction among these television audiences-turned-online followers revealed aspects of audience taste, audience segmentation and the use of social media. Findings illustrate that Muslim audiences in Malaysia are rather diverged due to a large amount of religious television programs. The diversity of the programs shown in television allows for audience to receive a variety of Islamic knowledge and contemporary religious issues. Muslim audiences now have access to an assortment religious programs with different hosts explaining and simplifying religious principles and practices. Caution, however, must be exercised when audiences display a rather intense preferences when acquiring religious knowledge through television. Unjustified reasons and obsessed emotions can interrupt the unity of Muslim society as whole and some form of vigilance should be observed for Islamic televangelism programs.